Immunotherapy "Shock" a case series of PD-L1 100% and pembrolizumab first-line treatment. (2017) - Zarogoulidis, Paul; Athanasiou, Evaggelia; Tsiouda, Theodora; Hatzibougias, Dimitrios; Huang, Haidong; Bai, Chong; Trakada, Georgia; Veletza, Lemonia; Kallianos, Anastasios; Kosmidis, Christoforos; Barbetakis, Nikolaos; Paliouras, Dimitrios; et al.
Abstract: In this decade a "bloom" of novel therapies has been observed for non-small cell lung cancer. We have new tools for the diagnosis of lung cancer and also we can re-biospy easier than before in different lesions and obtain tissue samples in order to investigate whether a patient can receive new targeted therapies. Immunotherapy has been well established previously for other forms of cancer, and nowadays it is also available for lung cancer. There are two immunotherapies for now nivolumab and pembrolizumab which can be administered as second line treatment, the second can also be administered as first-line if there is a programmed death-ligand 1 ≥50% expression.